(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Management planning prioritization is critical as a reference for managers when they try to improve the management effectiveness of marine protected areas. The objective of this study is to analyze the prioritization of Ay-Rhun MPA’s management planning using the Analytic Network Process. Problems and solutions in determining management priorities are clustered into four categories: ecology, economy, social, and institutional, and inside each cluster is sub-clusters based on the results of Focus Group Discussion. The results show that the main problem of Ay-Rhun MPA management is the ecology cluster. The sub-cluster analysis results showed that management problems should be addressed as priorities are: (1) the lack of human resource in terms of capacity and quantity; (2) the lack of understanding in conservation efforts; (3) price instability in fishery productions; (4) sand and coral mining for construction materials. Sub-cluster in a cluster could affect other elements in the same cluster, and it could also affect elements on different clusters. Therefore, recommendation strategies that should be prioritized to improve management effectiveness of Ay-Rhun MPA are (1) optimization of resource use based on carrying capacity, with the value of 0.6137; (2) MPA zonation design, with the value of 0.5484; (3) MPA management policy design, with the value of 0.5308; and (4) socialization regarding conservation efforts and understanding, with the value of 0.4680.